Periodontal considerations for orthodontists - Bastiaan Ross J. (Australasian Orthodontic Journal, 1998)
This paper presents the clinical orthodontist with a review of the relationship between periodontal health and orthodontic treatment. Stress is placed on the orthodontists responsibility to monitor periodontal health during therapy. Detection of a periodontal problem should prompt referral back to the general practitioner or periodontist.